발열유리 창호시스템의 발열량에 따른 실내공간 열적 쾌적성능 분석 - 강은호(Eun-Ho Kang); 김동수(Dong-Su Kim); 윤종호(Jong-Ho Yoon) (KIEAE Journal, 2021)
Purpose: In this study, an approach using the heated glazing window system as an auxiliary heating system is evaluated in terms of thermal comfort. Heat loss through window parts can occur relatively high because of low thermal resistance, which causes keeping lower surface temperature of the window, typically when outdoor air temperature is lower. With such issues, occupants may feel thermal discomfort near window parts mainly due to the radiant temperature asymmetry. In this study, an approach using the heated glazing window system as an auxiliary heating system is proposed to improve the performance of occupant‘s thermal comfort in a conditioned room. Method: For this analysis, a floor radiant heating system is considered as the main heat supply system in the conditioned zone. The internal thermal information of the room is calculated using a two-dimensional heat transfer analysis simulation (i.e., TRISCO). To quantitatively analyize the thermal comfort of the space adjacent to the window, the Predicted Mean Vote(PMV) at each point is derived by dividing the internal space into a two-dimensional grid. Result: As a result of the analysis, it was found that the heated glazing window system contributes to making the indoor thermal comfort uniform and can improve the thermal comfort of the window adjacent area. The maximum PPD deviation of the indoor space is about 6.3% when the heated glazing system is not operated, 1.8% under the heating of 20W/㎡, and 0.08% under the heating of 40W/㎡ KCI Citation Count: 0